2012
DOI: 10.1159/000338018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Infarct Pattern Caused by Vulnerable Aortic Arch Atheroma: DWI and Multidetector Row CT Study

Abstract: Background: Aortic arch atheroma (AAA) has been accepted as a possible embolic source in patients with ischemic stroke, especially cryptogenic stroke. However, despite its well-known role as a risk factor for stroke, research focused on the mechanism or characteristics of stroke caused by AAA is insufficient. In this study, we aimed to evaluate clinical and radiological characteristics including lesion pattern on DWI in acute stroke patients associated with vulnerable AAA detected by multidetector row computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
1
18
0
2
Order By: Relevance
“…[71][72][73] Aortogenic Embolic Source Evaluation TCD microembolism study showed that AAA has embolic potential, 74 and DWI patterns are characterized by multiple small scattered lesions in multiple vascular territories that are mainly located in cortical and borderzone regions. 75 These are in line with an autopsy study of cases with cerebral atheromatous embolism, which showed that atheromatous emboli containing mostly cholesterol crystals are associated with borderzone infarct, whereas large emboli containing fibrin are associated with large territory infarcts. 76 Therefore, additional workup to document aortogenic sources are recommended in elderly patients with vascular risk factor and infarct patterns associated with complex AAA; (1) multiple brain infarcts involving multiple vascular territories, 77 (2) small-sized infarcts, 65 and (3) location of cortical and borderzone region.…”
Section: Advanced Monitoring For Af Detectionsupporting
confidence: 87%
See 1 more Smart Citation
“…[71][72][73] Aortogenic Embolic Source Evaluation TCD microembolism study showed that AAA has embolic potential, 74 and DWI patterns are characterized by multiple small scattered lesions in multiple vascular territories that are mainly located in cortical and borderzone regions. 75 These are in line with an autopsy study of cases with cerebral atheromatous embolism, which showed that atheromatous emboli containing mostly cholesterol crystals are associated with borderzone infarct, whereas large emboli containing fibrin are associated with large territory infarcts. 76 Therefore, additional workup to document aortogenic sources are recommended in elderly patients with vascular risk factor and infarct patterns associated with complex AAA; (1) multiple brain infarcts involving multiple vascular territories, 77 (2) small-sized infarcts, 65 and (3) location of cortical and borderzone region.…”
Section: Advanced Monitoring For Af Detectionsupporting
confidence: 87%
“…76 Therefore, additional workup to document aortogenic sources are recommended in elderly patients with vascular risk factor and infarct patterns associated with complex AAA; (1) multiple brain infarcts involving multiple vascular territories, 77 (2) small-sized infarcts, 65 and (3) location of cortical and borderzone region. 75 …”
Section: Advanced Monitoring For Af Detectionmentioning
confidence: 99%
“…AAA was considered as a cause of stroke if vulnerable AAA was observed on the TEE or MDCT. Vulnerable AAA was defined as aortic plaques in the ascending aorta or proximal arch that met ≥1 of the following criteria: (1) ≥4 mm of intima–media thickness on TEE or ≥6 mm of thickness adjacent to the aortic wall on MDCT or (2) ulcerated plaque or (3) mobile plaque on TEE or soft plaque on MDCT . We performed the TEE or transcranial Doppler ultrasound agitated saline test or MDCT to evaluate PFO.…”
Section: Methodsmentioning
confidence: 99%
“…Vulnerable AAA was defined as aortic plaques in the ascending aorta or proximal arch that met ≥1 of the following criteria: (1) ≥4 mm of intima-media thickness on TEE or ≥6 mm of thickness adjacent to the aortic wall on MDCT or (2) ulcerated plaque or (3) mobile plaque on TEE or soft plaque on MDCT. 9,10 We performed the TEE or transcranial Doppler ultrasound agitated saline test or MDCT to evaluate PFO. PFO was deemed present when 1 of following criteria was observed: (1) the passage of >3 microbubbles to the left atrium within 3 cardiac cycles after complete opacification of the right atrium on the TEE, (2) microembolic signals within 40 seconds after injection of agitated saline with microbubbles on the transcranial Doppler ultrasound, or (3) a distinct flap in the left atrium at the expected location of the septum primum or a continuous column of contrast material connecting both atria or jet of contrast material into the right atrium on the MDCT.…”
Section: Patients and Workupsmentioning
confidence: 99%
“…In this study, advanced age and the low-density lipoprotein (LDL)cholesterol/high-density lipoprotein (HDL)-cholesterol ratio of 2.23 were substantially higher and closely associated with mobile and ulcerative aortic plaques. A study of 63 patients with cryptogenic stroke using diffusion-weighted MR imaging (DWI) and multidetector row CT revealed the presence of vulnerable aortic arch atheromatosis in 23.8% of the cases [16]. These patients had more risk of having a DWI pattern characterized by multiple, small, scattered lesions in multiple vascular territories [16].…”
Section: Cerebral Ischemia and Complex Athero-matosis Of The Aortic Archmentioning
confidence: 99%